Il y a un siècle, le mouvement pour le suffrage des femmes en Irlande - Máire Cross (Genre & Histoire)
The history of the struggle for the vote during the nineteenth and twentieth centuries coincides with nationalist struggles in many European countries. Similarities between campaigns for female suffrage between Finland and Ireland can be informative, but the complexity of the suffrage debate can only be appreciated through a detailed look at the little-known rich and turbulent national history. This article looks at how Irish historians have presented the question since the development of gender history. It explains the reasons for the invisibility of the suffrage question even though many women took part in Irish social and political campaigns north and south in Ireland at a critical time in the relationship with her neighbour and colonial power, Great Britain. National questions shaped the struggle, the outcome of gender relations in partitioned Ireland and overshadowed the writing of history.